Annual planning for swimming fitness - Rushall, B. S.
The article is adapted from NSWIMMING COACHING SCIENCE BULLETIN: Volume 2 Number 6 - July-August, 1994. It contains Editorial 1.Introduction 2.The Relationship of Basic to Specific Training 3.Planning Features Establishing objectives Testing programs General planning considerations 4.Training Phases in Annual Plans Transition phase Basic preparatory phase Specific preparatory phase Precompetition phase Competition phase Peaking Two-peak annual plan Excessive competitions plan Scholastic sports Planning 5.Closure 6.References It has been underlined, that there is no substitute for basic training as the structure upon which specific training is superimposed. That relationship, when employed correctly, will produce the highest level of performance possible in swimmers. To ignore one or the other is to lessen the value of training and subsequent "maximum" performances. At the 1994 US Swimming National Team Coaches' Meeting the value and need for basic training was echoed by several leading coaches who described it as the foundation for swimming excellence (Rushall, 1994b). Concern was expressed that rather than exploiting this necessity, many coaches were shying away from it in favor of "fad" programs or programs that stressed pure "quality and intensity" or excessive competitive schedules without forming an adequate base of training volume. This paper readdresses the need for solid foundational training that underlies almost all successful athletic performances.